Effect on adrenal function of topically applied clobetasol propionate (Dermovate). Issue 5997 (13th December 1975) - Allenby, C F; Main, R A; Marsden, R A; Sparkes, C G
Abstract : Thirty-nine patients (15 outpatients and 24 inpatients) with a variety of skin diseases affecting variable areas of the body surface were treated with clobetasol propionate ointment (Dermovate). Before and after treatment the adrenal response to an intramuscular injection of tetracosactrin was rested and additional 9 am plasma cortisol levels were measured at intervals during treatment. A satisfactory initial therapeutic response was achieved in almost all cases during the trial period. When more than 50 g of ointment a week was used a significant number of patients developed adrenal suppression. WHen less than 50 g per week was used any suppression tended to be transtion. These cysts may be the cause of this condition, producing abnormal amounts of ovarian steroids which modify the pituitary response. Futher studies are needed, however, to determine this possibility.